ANALISIS NILAI MORAL CERITA RAKYAT DAERAH TANAH BATAK TOBA - Marta Fretty Sihombing; Eddy Pahar Harahap; Siti Enik Mukhoiyaroh Bambang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to desribe and analyze the moral values contained in four folktales from the Batak Toba region, namely Putri Berdarah Putih, Baleo Mahato, Si Tangan Bulu, and Balige Raja. This research employs a qualitative method with a descriptive approach. The research dare were obtained from the folktale texts sourced using the Miles and Huberman (1994) model, which includes three stages: data reduction, data display, and conlusion drawing. The findings show that the four folktales contain moral values that reflect the worldview of the Batak Toba community. The identified moral values include honesty, responsibility, patience, religiosity, diligence and justice. These values are classified into three main aspects according to Nurgiyantoro (2010), namely the relationship between humans and God, humans and themselves, and humans and others or the social environment. The results of this study affirm that folktales play an important role as a medium of moral education and as a means of preserving the wisdom of Batak Toba people amid the currents of modernization.